Typology of Pork-Butcheries and Factors Determining the Sustainable Pork-Butcheries Waste Management in Southern Benin - Montcho, Marthe; ABOH, BOYA ANDRÉ; Séidou, Alassane Assani; Dayou, Ephrème Dossavi; PADONOU, Elie Antoine; BABATOUNDE, SÉVÉRIN; HORNICK, J.L (My University, 2018)
The butcheries are growing in Benin with a number of animal slaughtered on the rise. This slaughter practices generates more waste whose mismanagement can be a serious danger to the environment and public health. The aim of the study was assess the environmental impacts of pork-butcheries according to the types of butcheries in southern Benin. Observation and individual interviews were used in 80 randomly selected pork-butcheries. The data collected were analyzed with the FactoMineR package to perform a Principal Component Analysis (PCA) and to identify the different types of pork-butcheries according to their socioeconomic, hygienic and environmental characteristics. A multi-nominal logistic regression was also used to test waste management modes. Results from the study revealed three types of pork-butcheries which used different models for waste management. The pork-butcheries of type 1 are all young employees not member to any professional pork butcher's association. They don't have any waste management system. The pork-butcheries of type 2 are all entrepreneurs or pork-butcheries responsible. They are also affiliated with waste collection companies for the management of plastic waste. The type 3 differentiated by their great interest in the respect of hygienic standards and their frequent medical visit for professional purposes. The professional experience or seniority in the pork-butchery's activity, formal education and membership to a professional butcher's association are determinant variables of waste management produced by pork-butcheries. The implications of these results are discussed with respect to environment and waste management strategies for pork-butcheries.
Keywords: Environmental Impact; Meat Waste; Pork-Butcheries; Waste Management; Waste Water